The Association of Family-Related Adversity With Fighting in Adolescents: Does Hopelessness Mediate This Association? - Jaroslava Macková; Jaroslava Macková; Jaroslava Macková; Zuzana Dankulincova Veselska; Zuzana Dankulincova Veselska; Zuzana Dankulincova Veselska; Andrea Madarasova Geckova; Andrea Madarasova Geckova; Andrea Madarasova Geckova; Andrea Madarasova Geckova; Danielle Jansen; Jitse P. van Dijk; et al. (Frontiers Media S.A., 2021)
Objectives: To explore the association of family-related adversities with physical fighting, and whether this association is mediated by hopelessness.Methods: The sample consisted of 3712 Slovak adolescents (mean age: 13.9, 50.7% girls). Participants answered questions regarding experienced family-related adversities, involvement in physical fighting in the last 12 months and the Hopelessness Questionnaire. First, the association of family adversities in general with fighting and of each of family-related adversity separately was assessed using linear regression models and second, mediation was assessed using the a*b product method with bootstrapped 95% confidence intervalsResults: Adolescents who had experienced at least one family adversity reported more frequent fighting. Similarly, each of reported family adversities (death of a parent, substance abuse problems of a parent, conflicts/physical fights, divorce) was associated with more frequent fighting among adolescents. The mediation effect of hopelessness was found in each association of family-related adversity with fighting.Conclusion: These findings suggest that interventions to support adolescents who had experienced family adversities could among other things be directed at better coping with hopelessness.